Ultrasound‐Induced Wireless Energy Harvesting for Potential Retinal Electrical Stimulation Application. (27th May 2019) - Jiang, Laiming; Yang, Yang; Chen, Ruimin; Lu, Gengxi; Li, Runze; Xing, Jie; Shung, K. Kirk; Humayun, Mark S.; Zhu, Jianguo; Chen, Yong; Zhou, Qifa
Abstract: Retinal electrical stimulation for people with neurodegenerative diseases has shown to be feasible for direct excitation of neurons as a means of restoring vision. In this work, a new electrical stimulation strategy is proposed using ultrasound‐driven wireless energy harvesting technology to convert acoustic energy to electricity through the piezoelectric effect. The design, fabrication, and performance of a millimeter‐scale flexible ultrasound patch that utilizes an environment‐friendly lead‐free piezocomposite are described. A modified dice‐and‐fill technique is used to manufacture the microstructure of the piezocomposite and to generate improved electrical and acoustic properties. The as‐developed device can be attached on a complex surface and be driven by ultrasound to produce adjustable electrical outputs, reaching a maximum output power of 45 mW cm −2 . Potential applications for charging energy storage devices and powering commercial electronics using the device are demonstrated. The considerable current signals (e.g., current >72 µA and current density >9.2 nA µm −2 ) that are higher than the average thresholds of retinal stimulation are also obtained in the ex vivo experiment of an implanted environment, showing great potential to be integrated on implanted biomedical devices for electrical stimulation application. Abstract : A potential electrical stimulation strategy using ultrasound‐driven wireless energy harvesting technology is presented to convert acoustic energy into electricity through a mm‐scale ultrasonic energy harvesting device that is flexible and lead‐free. The as‐developed device can be attached on a complex surface and be driven by ultrasound to produce adjustable electrical outputs, reaching a maximum output power of 45 mW·cm −2 .